Highly conductive polypropylene‐based composites for bipolar plates for polymer electrolyte membrane fuel cells. Issue 2 (15th February 2021) - Bühler, Roman; Thommen, Moritz; Le Canut, Jean‐Marc; Weber, Jean‐Francois; Rytka, Christian; Tsotra, Panagiota
Abstract: This work focuses on the development of innovative polymer‐based composites suitable for fuel cell bipolar plates. The developed composites need to fulfil the given requirements concerning electrical and thermal conductivity, mechanical properties, and additionally ensure easy implementation in industry. Various potentially suitable electrically conductive fillers, such as graphite, carbon black, carbon fibers, carbon nanotubes, and expanded graphite are added to a polypropylene (PP) matrix. The samples are tested with regard to their through‐plane electrical conductivity, in‐plane thermal conductivity, flexural properties, and corrosion resistance. The effect of plate thickness and filler composition is systematically investigated. It is also found that the electrode area and the applied pressure during the electrical resistance measurements have a significant effect on the electrical conductivity. The materials show very good processability with compression molding, which results in the maximum electrical conductivity of 46 S cm −1, using a multi‐filler approach with carbon‐based fillers of different forms and sizes. These results meet or even exceed those found in the literature, and it is strongly believed that optimization of the manufacturing process can result in an electrical conductivity value above the target of 50 S cm −1 .